(untitled) (Al-Aasar, 2025)
The appointment of judges holds a central position in the administration of justice, both in Islamic jurisprudence and in contemporary constitutional systems. Islamic law outlines a set of rigorous criteria for judicial appointment, emphasizing integrity, justice, scholarly competence, and moral uprightness. These principles were consistently reflected in early Islamic governance, where the selection of judges was based on merit, accountability, and adherence to the higher objectives of Shariah. In Pakistan, the constitutional framework particularly provisions related to the judiciary sets forth a structured mechanism for judicial appointments through bodies such as the Judicial Commission and the Parliamentary Committee. This research undertakes a comparative analysis of the Islamic principles of judicial eligibility and the constitutional mechanism of judicial appointments in Pakistan. The study highlights points of convergence and divergence between the two systems while examining how effectively the contemporary framework aligns with the classical ideals of justice, impartiality, and institutional integrity. The findings suggest that while Pakistan’s judicial appointment structure incorporates several Shariah-based values, practical challenges persist, necessitating reforms to enhance transparency, meritocracy, and public confidence in the judicial institution.